Functional characterization of Citrus macrophylla BOR1 as a boron transporter. Issue 3 (25th March 2013) - Cañon, Paola; Aquea, Felipe; Rodríguez‐Hoces de la Guardia, Amparo; Arce‐Johnson, Patricio
<x xml:space="preserve">Abstract</x> Plants have evolved to develop an efficient system of boron uptake and transport using a range of efflux carriers named BOR proteins. In this work we isolated and characterized a boron transporter of citrus (Citrus macrophylla), which was named CmBOR1 for its high homology to AtBOR1. CmBOR1 has 4403 bp and 12 exons. Its coding region has 2145 bp and encodes for a protein of 714 amino acids. CmBOR1 possesses the molecular features of BORs such as an anion exchanger domain and the presence of 10 transmembrane domains. Functional analysis in yeast indicated that CmBOR1 has an efflux boron transporter activity, and transformants have increased tolerance to excess boron. CmBOR1 is expressed in leaves, stem and flowers and shows the greatest accumulation in roots. The transcript accumulation was significantly increased under boron deficiency conditions in shoots. In contrast, the accumulation of the transcript did not change in boron toxicity conditions. Finally, we observed that constitutive expression of CmBOR1 was able to increase tolerance to boron deficiency conditions in Arabidopsis thaliana, suggesting that CmBOR1 is a xylem loading boron transporter. Based on these results, it was determined that CmBOR1 encodes a boric acid/borate transporter involved in tolerance to boron deficiency in plants.